Mensuração dos níveis de resiliência de mulheres que sofreram aborto espontâneo - Souza, Lidia Dayse Araujo de (2017)
Abortion can be defined as spontaneous or induced expulsion of the fetus weighing less than 500g. Abortion is classified as spontaneous when natural expulsion of the fetus occurs before the twentieth week of pregnancy. When there is the use of some mechanism of induction is called abortion provoked. The existence of a process of mourning for spontaneous abortion is accompanied by depressive reactions and a compulsive search for new pregnancies. In addition to political, religious and physical problems, abortion can also severely affect women's psychic health and resilience. This is defined as being human capacity to overcome challenges and difficulties, and to experience a healthy development after exposure to risks. Resilient people respond better to challenges and situations, according to their internal and external dynamics, as well as the efficiency and quality of their responses, in the face of a new situation. The project has been approved by the Ethics and Research Committee to which it was submitted through the Brazil Platform. The present study has the objective of analyzing the level of resilience of women who suffered miscarriage and who were attended at a referral maternity hospital. As an alternative to study this type of population, the Network Scale Up method was efficient because it is used to estimate social network sizes with a rare characteristic. Thus, the method estimated the size of the target population in João Pessoa, is approximately 2,512 women. In this context, the sample consisted of 52 women aged between 18 and 35 years, who underwent abortion in the period studied. It was possible to observe that most of these women declared themselves to be brown (96%), with a mean age of 29 years, single (31%), but with stable union (55%) and love relationship with the baby's father (62%). It was also possible to see that 69% had incomplete secondary education and 60% were unemployed, more than half did not have a home (67%), 19% had had previous abortions, (81%) planned the pregnancy.Regarding resilience, the CD-RISC10 considered the low level of resilience (65%) of the women studied. The present study shows the importance of effective public policies to assist women seeking care due to the occurrence of abortion. In all its context, not only physical but psychological and emotional, making use of risk and protection factors as strategies to help it increase its level of resilience and not develop other diseases. It was notorious in this study the influence of the age of the women and the amount of children in relation to the level of resilience, that is, an older woman with fewer children is able to have lower levels of resilience.